2009
DOI: 10.1136/emj.2008.059188
|View full text |Cite
|
Sign up to set email alerts
|

The health behaviour and clinical characteristics of ambulance users with acute asthma

Abstract: Ambulance users with acute asthma are more likely to be older, married and less educated. There is no evidence that this group is less responsible in managing their health; however, fewer ambulance users attended their follow-up appointment and the implication for ongoing care requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…24 Respiratory problems have been identified as a common reason for calling an ambulance service in the USA, where 12% of encounters have been categorised as 'respiratory distress'. 25 Although research studies have described the epidemiology and outcomes of ambulance service users with respiratory distress, [25][26][27][28] they have focused on patients who are transported to emergency departments rather than those not conveyed. We could find only one study of non-conveyance of patients with breathing difficulties that focused on the impact of advanced paramedics on this condition.…”
Section: International Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…24 Respiratory problems have been identified as a common reason for calling an ambulance service in the USA, where 12% of encounters have been categorised as 'respiratory distress'. 25 Although research studies have described the epidemiology and outcomes of ambulance service users with respiratory distress, [25][26][27][28] they have focused on patients who are transported to emergency departments rather than those not conveyed. We could find only one study of non-conveyance of patients with breathing difficulties that focused on the impact of advanced paramedics on this condition.…”
Section: International Perspectivementioning
confidence: 99%
“…Internationally, a small number of research studies have been undertaken to describe the epidemiology and outcomes of ambulance service users with respiratory distress or breathing problems. [25][26][27][28] As stated in the introduction to this report, these studies focused on patients who were transported to emergency departments rather than those who were not conveyed. A study of the impact of advanced paramedics on admission rates of people calling 999 with breathing difficulties identified a hospital admission rate of 15% (18/119) within 72 hours for those attended by an advanced paramedic.…”
Section: Summary Of Findings In the Context Of Other Researchmentioning
confidence: 99%
“…They pointed to possible connections between lower education, lower professional qualifications, and limited employment opportunities that may increase the likelihood of finding work in jobs with a higher exposure to environmental risk factors. In another example, Smith et al [30] found that asthma patients in the United States who were ambulance users tended to have lower levels of education. They suggested that a lack of access to public or private transportation among these populations may increase their likelihood of using ambulance services to seek medical care.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies conducted in the UK and Australia, researchers reported comparable or higher rates of ambulance use (26%-58%), and stated that the optimal rate is not known and probably varies depending on assessment of risk and personal attitudes. 22,23 Thus, costly ambulance use for asthma requires further investigation and is another potential area for patient education.…”
Section: Discussionmentioning
confidence: 99%